Supraspinal and Peripheral, but Not Intrathecal, σ1R Blockade by S1RA Enhances Morphine Antinociception - Vidal-Torres, Alba; Fernández-Pastor, Begoña; Carceller, Alicia; Vela, José Miguel; Merlos, Manuel; Zamanillo, Daniel (Frontiers in Pharmacology, 2019)
Sigma-1 receptor (σ1R) antagonism increases the effects of morphine on acute nociceptive pain. S1RA (E-52862) is a selective σ1R antagonist widely used to study the role of sigma-1 receptors. S1RA alone exerted antinociceptive effect in the formalin test in rats and increased noradrenaline levels in the spinal cord, thus accounting for its antinociceptive effect. Conversely, while systemic S1RA failed to elicit antinociceptive effect by itself in the tail-flick test in mice, it did potentiate the antinociceptive effect of opioids in this acute pain model. The present study aimed to investigate the site of action and the involvement of spinal noradrenaline on the potentiation of opioid antinociception by S1RA on acute thermal nociception using the tail-flick test in rats. Local administration was performed after intrathecal catheterization or intracerebroventricular and rostroventral medullar (RVM) cannulae implantation. Noradrenaline levels in the spinal cord were evaluated using the concentric microdialysis technique in awake, freely-moving rats. Systemic or supraspinal administration of S1RA alone, while having no effect on antinociception, enhanced the effect of morphine in rats. However, spinal S1RA administration did not potentiate the antinociceptive effect of morphine. Additionally, the peripherally restricted opioid agonist loperamide was devoid of antinociceptive effect but produced antinociception when combined with S1RA. Neurochemical studies revealed that noradrenaline levels in the dorsal horn of the spinal cord were not increased at doses exerting potentiation of the antinociceptive effect of the opioid. In conclusion, the site of action of σ1R for opioid modulation on acute thermal nociception is located at the peripheral and supraspinal levels, and the opioid-potentiating effect is independent of the spinal noradrenaline increase produced by S1RA.